Comparative in vivo evaluation of cross-linked and non-cross-linked collagen membranes for guided bone regeneration in rat calvarial defects - Baggio, Ana Maira Pereira [UNESP]; Viotto, Arthur Henrique Alécio [UNESP]; Delamura, Izabela Fornazari [UNESP]; Bizelli, Vinicius Ferreira [UNESP]; Jacob, Ricardo Garcia Mureb [UNESP]; Deus, Ciro Borges Duailibe de [UNESP]; Neiva, Rodrigo Faria [UNESP]; Faverani, Leonardo Perez [UNESP]; Bassi, Ana Paula Farnezi [UNESP] (FapUNIFESP (SciELO), 2025)
Guided bone regeneration (GBR) is a critical strategy for repairing large bone defects. This study aimed to assess the osteopromotive potential of a porcine cross-linked collagen membrane in critical calvaria-defects in rats. Seventy-two rats were divided into three groups: blood clot (CG - negative control), Bio-Gide® membrane (BG - positive control), and Ossix Plus® membrane (OSX - test). The defects were covered according to each group, and the experimental times were 7, 15, 30, and 60 days postoperatively. The collected samples were evaluated by histometric analysis, inflammatory profile, immunohistochemistry, and micro-computed tomography (micro-CT). At 7 days, no significant differences in bone neoformation were observed. At 15 days, the OSX group showed increased new bone formation compared to CG (p = 0.031). At 30 days, the BG group exhibited the most significant increase compared to both OSX (p < 0.001) and CG (p < 0.001). At 60 days, OSX demonstrated the highest osteopromotive potential, significantly outperforming CG (p < 0.001) and BG (p < 0.001). MicroCT analysis revealed that the OSX group had a bone volume (BV) of 17.33 ± 1.74 mm3, significantly higher than BG (8.06 ± 1.26 mm3, p < 0.05). The cross-linked collagen membrane was biologically more favorable for bone regeneration being a promising option for GBR procedures.